PENGARUH KUALITAS PELAYANAN, HARGA, PROMOSI, KEAMANAN TRANSAKSI, DAN LOYALITAS PERUSAHAAN TERHADAP PENGAMBILAN KEPUTUSAN PEMBELIAN TIKET PESAWAT ONLINE PADA APLIKASI TRAVELOKA - Dila Damayanti; Gede Elvin Febri Sudarmanto (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2021)
Based on the t test results, the quality of service has a significant effect on purchasing decisions with a significance value of 0.008 smaller than 0.05 (0.008 < 0.05), meaning the quality of service has a significant influence on the purchase decision. The price significantly affects the purchase decision with a significance value of 0.000 smaller than 0.05 (0.000 < 0.05), which means that the price has a significant influence on the purchase decision. Promotion significantly affects the purchase decision with a significance value of 0.047 smaller than 0.05 (0.047 < 0.05), meaning the promotion has a significant effect on the purchase decision. Transaction security significantly affects purchase decisions with a significance value of 0.017 less than 0.05 (0.017 < 0.05), meaning transaction security has a significant effect on the purchase decision. Company loyalty significantly affects the purchase decision with a significance value of 0.037 smaller than 0.05 (0.037 < 0.05), meaning company loyalty has a significant influence on purchasing decisions.